Carrying capacity of an estuary for prawn farming - Bong, Alvin Chee Hong (Universiti Malaysia Sarawak, (UNIMAS), 2005)
Enrichment of organic matter in the sediment occurred when the carrying capacity of an estuary for prawn fanning has been exceeded. By determining the organic matter in the sediment, the carrying capacity which will be basis for authority to issue license was detennined. Subsequently, a scientific based estuarine management strategy that provides infonnation in advance, to support planning and managemen~ to ensure sustainable development of P. monodon fanning was fonnulated. Carrying capacity indicator chart and a simple mathematical fonnula (organic matter model) were developed for estimating the carrying capacity using the sediment quality (indicator) data obtained. In this study, sediment traps were fabricated and deployed at Ketup, Sebandi and Asajaya Laut (control) watergates in Asajaya catchment to trap the suspended sediment discharged from the prawn fanns) Grab sampling using vertical acrylic cylinder and Mackenzie's bottom grab sampler were also carried out for collecting water samples and sediment samples at these watergates. Data on the existing physical environment, acreage of ponds harvested, effluent discharged during harvesting, yield of P. monodon and feed used for harvested P. monodon culture were obtained from the field observations and interviews. The sediment traps have been proven useful for collecting fresh sediment from the activities of prawn fanning in the study area. Trapped sediment has significantly higher (p<O.05) content of organic matter compared to the grab sediment in Ketup and Sebandi. Acreage of ponds harvested, feed and yield were identified as possible pollutant sources that may contribute to the carrying capacity of an estuary for P. monodon fanning through the enrichment of orgallic matter. The proposed carrying capacity indicator chart results showed that carrying capacity for prawn fanning in Sebandi may have been exceeded.